School Perspectives on The Implementation of Adaptive Physical Education in Cirebon City - Anggara, Muhammad Sofyan; Suherman, Adang; Hendrayana, Yudy (Universitas Pendidikan Indonesia, 2023)
This study aims to determine the perspectives of special schools regarding the implementation of adaptive physical education in Cirebon City. The research method employed in this study is a descriptive qualitative approach. Data collection techniques involve the use of the Triangulation method. Data analysis in this study utilizes the Miles and Huberman field models. The sampling technique utilizes random sampling. Based on the research findings and the discussions presented, it can be concluded that the initial implementation of adaptive physical education for children with special needs can be considered successful because it has achieved the objectives of adaptive physical education. Furthermore, the treatment provided by physical education teachers to children with special needs is consistent with that provided to regular students, with special modifications to enable children with special needs to participate in the same learning materials as their peers. However, the third observation indicates that not all lessons align with the previously created lesson plans (RPP). Teachers have more flexibility to adapt to the circumstances and conditions of both regular students and children with special needs. The four strategies for adaptive education include learning modification techniques, environmental modification techniques, and learning activity modification techniques.